Kerjasama Otoritas Jasa Keuangan (OJK) Dengan Monetary Authority Of Singapore (MAS) Dalam Bidang Teknologi Finansial - Malchan, Muhammad Ilyas Balya; Ismiyatun, Ismiyatun (Kajian Hubungan Internasional, 2022)
This research discusses globalization and the technological revolution, which is increasingly developing technology and information. The mobilization of the world community is also growing and more complex. This is what triggers globalization to occur because trade and financial movements can become easier to do. The author wants to describe the objectives and reasons for the Financial Services Authority in collaboration with the Monethary Authority of Singapore in the field of financial technology. By using the theory of National Interest, which is defined as the ability of a country to protect its physical identity, political identity and cultural identity. National interest is both a tool and a goal to be used as a medium to achieve the national goals of a country. The level of analysis used is the domestic influence because it is related to activities that occur at the country level. The type of research in this paper is qualitative analytic with secondary data. The author also describes the background for the formation of cooperation, the dynamics in the continuity of cooperation and the condition of financial technology in Indonesia. At the end of the research, the reasons for the cooperation between OJK and MAS are explained, namely technological developments, strengthening economic foundations and information exchange.